Synthesis and Theoretical Study of Gadolinium(III) Complex of Heptadentate (N4O3) Tripodal Schiff Base Ligand - IZADKHAH*, VIDA; SALEHZADEH, SADEGH; GOLBEDAGHI, REZA; BAYAT, MEHDI; DAVOODI, LEILA (Asian Journal of Chemistry, 2010)
A new potentially heptadentate (N4O3) Schiff base ligand N[(CH2)2N = CH(2-OH-5-BrC6H3)]2[(CH2)3N = CH(2-OH- 5-BrC6H3)] (H3L) was synthesized and characterized by elemental analysis and various spectroscopic methods. This ligand was derived from the condensation reaction of a tripodal tetraamine ligand, bis(2-aminoethyl)(3-aminopropyl) amine (pee) with 3 equiv. of 5-bromosalicylaldehyde. The neutral gadolinium(III) complex of this bulky ligand was also synthesized. The complex was characterized by microanalysis and IR spectra. The capability of H3L as well as its unsubstituted analogs to encapsulate a lanthanide ion, herein La(III), has been theoretically studied by ab initio restricted Hartree-Fock (RHF) and density functional B3LYP methods.